A Novel Visible Range FRET Probe for Monitoring Acid Sphingomyelinase Activity in Living Cells - Kappe, Christian (Chemistry, 2020)
Activity of acid sphingomyelinase has been implicated in a number of diseases like acute lung injury, sepsis or metastasis of melanoma cells. Here, we present a sphingomyelinase FRET probe based on FAM/BODIPY dyes for real‐time monitoring of acid sphingomyelinase. The probe gives rise to a tremendous increase in fluorescence of the fluorescein FRET donor upon cleavage and we show that this is, to a significant part, due to cleavage‐associated phase transition, suggesting a more systematic consideration of such effects for future probe development. The probe allows for the first time to monitor relative sphingomyelinase activities of intact living cells by flow cytometry.